2009
DOI: 10.1007/s11258-009-9605-4
|View full text |Cite
|
Sign up to set email alerts
|

Biparental inbreeding depression, genetic relatedness and progeny vigour in a wind-pollinated treeline species in Argentina

Abstract: Spatially restricted gene flow and resulting spatial genetic structure are generally considered as being the primary controlling factors in the dynamics of biparental inbreeding depression in a wide range of plant species. However, wind-pollinated angiosperm trees have not been studied adequately in this respect. The present study analyses the relationships among parental genetic similarity, outcrossing distances, progeny vigour and mortality in Polylepis australis (Rosaceae), a wind-pollinated treeline specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 55 publications
3
20
0
2
Order By: Relevance
“…The overall means of polymorphic bands (P = 92.3 %) found in this analysis were in accordance with those reported for Polylepis australis by JULIO et al, (2008: ISSR, P = 89-91%) and SELTMANN et al, (2009b: RAPD, P = 75-82%). The similar values of P at different criteria indicates that alleles in several loci are present in similar frequencies throughout the whole population, which is presumably promoted by a high degree of gene flow (Nm = 10.9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall means of polymorphic bands (P = 92.3 %) found in this analysis were in accordance with those reported for Polylepis australis by JULIO et al, (2008: ISSR, P = 89-91%) and SELTMANN et al, (2009b: RAPD, P = 75-82%). The similar values of P at different criteria indicates that alleles in several loci are present in similar frequencies throughout the whole population, which is presumably promoted by a high degree of gene flow (Nm = 10.9).…”
Section: Discussionsupporting
confidence: 90%
“…Studies conducted by SELTMANN et al (2009b) in the same areas indicate that there has been no decline in the naturally deposited outcrossed pollen load in small P. australis forest fragments, and that isolated forest fragments are not subject to inbreeding depression through selfing. However, a molecular study in two fragments within the Yuspe and Los Molles basins (JULIO et al, 2008) found evidence of genetic fragmentation only in young trees, suggesting fragmentation effects might be a problem in the future; as has also been found in other South American trees where fragmentation has been recent (MATHIASEN et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Inbred offspring would not have survived during either stage of the life cycle, such as at seed production, germination, seedling growth stages, and so on, whereas outcrossed progeny having relatively higher fitness have a higher probability of survival to the present time. Such a positive relationship between the genetic relatedness of parents and offspring fitness has also been observed in other plants (Hirao 2010;Seltmann et al 2009;Wagenius et al 2010). Our results were inferred from dominant markers, which have lower powers than microsatellites in sibship and parentage assignments (Gerber et al 2000).…”
Section: Discussionsupporting
confidence: 65%
“…(Rosaceae) consists of ∼30 species growing in Andean montane forests and tree line habitats from Venezuela to central Argentina Schmidt-Lebuhn et al 2007). Polylepis is one of relatively few wind-pollinated genera in the Rosaceae (Schmidt-Lebuhn et al 2007;Seltmann et al 2009), and species of Polylepis are known to hybridize with each other (Simpson 1986;Romoleroux 1996;Schmidt-Lebuhn et al 2006;Segovia et al 2012). The genus has further been shown to include both diploid and polyploid (tetra-and octoploid) taxa Location of our study sites (black circles) and pie charts reflecting the proportion of ploidy levels found at each Polylepis australis site in Argentina (A) and the Sierras de Có rdoba (B).…”
Section: Introductionmentioning
confidence: 99%
“…In the north of its range, P. australis co-occurs or grows in close proximity to four other species of Polylepis, whereas in the Sierras de Có rdoba, it is the only species of the genus (Hensen et al 2011). Studies on the mating system of P. australis have revealed high pollen viability and longevity and high effective pollen flow (Seltmann et al , 2009. Fruits are single-seeded nutlets that are dispersed over short distances by wind.…”
Section: Introductionmentioning
confidence: 99%